優質教學案例指標建構之研究 A Study on the Construction of Criteria for Good Teaching Cases - 李雅婷 Ya-Ting Lee; 葉晉嘉 Chin-Chia Yeh; 陳為彤 Wei-Tung Chen (National Changhua University of Education, 2016)
教育向來追求更好的教學法來提升學生學習成效，本研究背景亦是緣自於研究者任教於師資培育機構過往教學經驗。研究者自多年前將案例教學法融入師資培育課程，亦引導師資生將教學實習經驗再書寫成教學案例，透過此歷程，可以讓師資生熟悉案例，瞭解 案例研究的進行等，有助於提升專業性。然而，在這引導過程發現，國內外似乎尚未有優質案例指標用以評估案例的良窳。基於上述背景，本研究目的如下：（一）建構優質教學案例指標。（二）建構優質教學案例細項指標相對權重。為達目的，本研究採德懷 術與層級分析法，經三次問卷調查，獲得以下結論：（一）優質案例指標建構有助於師資培育者選擇或發展優質之教學案例。（二）評定優質案例宜包含四個構面與二十一個指標，其中首重內容概念。（三）運用本指標宜依各構面指標的重要程度加權。本研究 所建構之案例指標用以篩選優質案例，但仍有待其他因素配合才能提高案例的教學效能。最後提出建議如下：（一）應用本案例指標引導發展優質教學案例。（二）擴展本案例指標至其他案例形式或增加構面。 It has always been the pursuit of better teaching methods to improve students' learning outcomes for educators. The background of this study was originated from the past teaching experiences that the researchers have obtained while teaching at a teacher training institution. The researchers have integrated the case method into the teacher education curriculum for many years as well as guided the pre-service teachers to rewrite their internship experiences into teaching cases. The process enabled the pre-service teachers to be familiar with the theme cases and understand how to conduct case studies, which helped develop their professionalism. However, based on our experiences, it appears that there is as yet a lack of criteria for evaluating quality teaching cases. Therefore, the purposes of this study were as follows: (1)constructing a set of criteria for good teaching cases, and (2) settling the relative weight of each indicator within a set of criteria for good teaching cases. To reach the goal, the researchers adopted the Delphi Method and Analytical Hierarchy Process in this study. The questionnaire survey was repeated three times, leading to the following conclusions: (1) the construction of a set of criteria for quality teaching cases was found to facilitate teacher trainers to choose or develop good teaching cases, (2) in order to evaluate high quality teaching cases, it was necessary to include in the set of criteria a total of 21 indicators along four dimensions, the most important dimension being conceptual contents, and (3) it is necessary to take into account the relative weight of each indicator for a given dimension while applying the set of criteria to the evaluation of a teaching case. The criteria constructed in this study were used for the selection of quality cases. Nevertheless, in order to enhance their instructional effectiveness, it may be necessary to incorporate the teaching cases with other factors. There were suggestions as the following: first, applying the set of criteria developed in this study as a guide to the development of high-quality teaching cases, and second, extending the set of criteria to cover other case formats or to include additional dimensions.